PTU-031 Outcomes from an international multicentre registry of patients with gastrointestinal bleeding undergoing endoscopic treatment with hemospray. (17th June 2017) - Alzoubaidi, D; Magee, C; Gulati, S; Haji, A; Morris, J; Lovat, L; Hayee, B; Haidry, R
Abstract : Introduction: Acute gastrointestinal bleeding (G.I.B) carries a poor prognosis unless prompt endoscopic haemostasis is achieved. Hemospray is a novel proprietary mineral blend that forms a mechanical barrier over the bleeding site when applied endoscopically. The primary aim of this international multicentre registry is to collect data on the successful endoscopic haemostasis of GI bleeding with Hemospray. Secondary outcomes are re-bleeding (within 72 hours), device safety and adverse events related to the treatment. Method: Data were collected prospectively (January 2016 – October 2016) on the use of Hemospray in acute upper and lower G.I.B, from two initial centres in the international registry. The use of hemospray in GI bleeding was at the endoscopist's discretion. Hemospray use was either as mono therapy, as dual-therapy with standard endoscopic measures or as rescue therapy once standard methods had failed. Results: To date 36 cases have been recruited (27 male and 9 female). Hemospray was used in 15 patients (42%) as monotherapy, in 17 patients (47%) in combination with other modalities and in 4 patients (11%) used as rescue therapy where other modalities failed. The Forrest Classification of the bleeding lesion were in 7 (19%) cases Forrest Ia bleed, 23 (64%) Ib, 2 (6%) IIa, 2 (6%) IIb and 2 (6%) Forrest III bleed. Sources of G.I.B included Peptic Ulcer disease 17 (47%), Post endoscopic Therapy 8 (22%), Malignancy 6 (17%), inflammation 2 (6%), Duodenal diverticulum bleed 1 (3%), Post Radiation bleed 1 (3%) and Variceal Bleed 1 (3%). 8 patients (22%) were anticoagulated at the time of emergency endoscopy. 31 patients (86%) achieved immediate haemostasis after hemospray endoscopic therapy. There were 5 cases (14%) of re-bleeding of which 2 (6%) were immediate and 3 (8%) occurred more than 7 days later. Hemospray was used in combination with other modalities in all these 5 cases. Of these 3 passed away, 1 required radiological embolisation and 1 patient was stabilised with conservative management. There were no reported immediate or delayed complications from the treatment. Conclusion: Early data from our registry show a high rate of immediate haemostasis (86%) with hemopsray and an excellent safety profile. The iminnet expansion of this registry to other centres in Europe will provide invaluable data on the efficacy of Hemospray in various disease and patient types over the coming years. Disclosure of Interest: None Declared